(untitled) (American Journal of Islam and Society, 2018)
When I first walked into the living quarters of Begum Noor Jahan Zareef Thanawi (1931-2017) in Karachi, I was fatigued from jetlag and not expecting much to come of the meeting except polite verbal exchanges. But as I absorbed the functionality of every item in the sparsely furnished room, and the immense level of spiritual focus she carried within her frail (though still somehow strong!) physical frame, I realized I was sitting in the company of no ordinary woman. It was about Begum Zareef that Dr. ‘Abd al-Hayy ‘Arifi—one-time nāẓim of Dar al-‘Ulum Karachi and spiritual successor to Ashraf ‘Ali Thanawi—had remarked, “If we gave khilāfat (spiritual successorship) to women, we would have given it to her.” Though not given permission to take spiritual disciples, her sheikh had given her a general allowance to teach the religious sciences to women. She taught Qur’anic exegesis (tafsīr) for decades out of her home; wrote numerous pamphlets on spirituality and religious practice; and published a volume on the legal rulings of Hajj, with a special focus on related women’s issues. If Begum Zareef were asked what was the secret that persuaded her sheikh to give her such a wide allowance to teach, I know her answer would be the pious company (of her sheikh and others) that she kept throughout her life. As Ashraf ‘Ali Thanawi clarifies in Fawāʾid al-ṣuḥba, his famous lecture cited by Darakhshan Khan, it was the ṣuḥba (company) they’d kept that made the Companions (Ṣaḥāba) who they were. Were it not for the fact that they had sat with the Messenger of God, they would not have attained their otherwise unattainable spiritual and religious rank, and they would not be seen as a necessary source of religious knowledge for all Muslims who came after them. In my own book,1 I argue that ṣuḥba, in fact, lies at the spiritual center of Sunni Islam. For one to be a “real Sunni,” one does not merely have to accept the probity of every one of the Ṣaḥāba; one must also accept that the preservation and continuation of true religious ...